When should video be added to conventional urodynamics in adults and is it justified by the evidence? ICI‐RS 2014. Issue 2 (February 2016) - Anding, Ralf; Rosier, Peter; Smith, Phillip; Gammie, Andrew; Giarenis, Ilias; Rantell, Angela; Thiruchelvam, Nikesh; Arlandis, Salvador; Cardozo, Linda
Abstract : Aims: To debate and evaluate the evidence base regarding the added value of video to urodynamics in adults and to define research questions. Methods: In the ICI‐RS Meeting 2014 a Think Tank analyzed the current guidelines recommending video urodynamics (VUD) and performed a literature search to determine the level of evidence for the additional value of the imaging with urodynamic assessment of both neurogenic and non‐neurogenic lower urinary tract dysfunction. Results: Current guidelines do not specify the added value of imaging to urodynamics. Recommendations are based on single center series and expert opinion. Standard imaging protocols are not available and evidence regarding the balance between number and timing of pictures, patient positioning, and exposure time on the one hand and diagnosis on the other hand is lacking. On the basis of expert consensus VUD is relevant in the follow‐up of patients with spinal dysraphism. Evidence for the value of VUD in non‐neurogenic lower urinary tract dysfunction is sparse. There is some evidence that VUD is not necessary in uncomplicated female SUI, but expert opinion suggests it might improve the evaluation of patients with recurrent SUI. Conclusions: There is only low level evidence for the addition of video to urodynamics. The ICI‐RS Think Tank encourages better reporting of results of imaging and systematic reporting of X‐ray doses. Specific research hypotheses regarding the added value of imaging are recommended. The panel suggests the development of standards for technically optimal VUD that is practically achievable with machines that are on the market. Neurourol. Urodynam. 35:324–329, 2016 . © 2016 Wiley Periodicals, Inc.